Pengaruh Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) Terhadap Hasil Belajar Keliling dan Luas Bangun Datar Kelas IV SD - Nurul Hidayah; Syafri Ahmad (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This study aims to determine he Influence of the Indonesian realictic mathematics education approach (PMRI) on learning outcomes in learning flat circumference and wide shape in class IV of SDN Cluster III  in the sub-district of Payakumbuh of the 2019/2020 accademic year  in the odd semester. This research is a quantitative  study with a type experimental reseacrh quasi- experimental research technique and way of taking the sampel is simple random sampling. The population is 85 paticipant, with a sample of 46 prticipant. Based of the research  yhat has been done, obtained t-count> t-table that 6,22 > 1,68 with α = 0.05 which means that Ho is rejected, so Ha is accepted, it meaning there is an Influence of the the Indonesian realictic mathematics education approach (PMRI)  in Learning wide and flat wake circumference in class IV of SDN Cluster III  in the sub-district of Payakumbuh